Tour operators and operations : development, management and responsibility - Holland, Jacqueline; Leslie, David (United Kingdom : CABI, 2018)
"The package tour is still a key component of the tourism sector, but recently, these packages have changed from the traditional 'sand, sun, and sea' to a shift in composition involving a myriad of niche products. In addition, a major increase in tour operator activity in the major emergent economies of the world has been witnessed. With a focus on the creation and distribution of packaged holidays, this text covers the fundamentals of business and the relationship between the operators and destinations, with particular reference to the sustainability of both parties. International cases studies are included throughout."--Provided by publisher. Focusing on the creation and distribution of packaged holidays, this text covers the fundamentals of business and the relationship between tour operators and destinations. With particular reference to sustainability, it provides a wealth of information regarding eco, nature and adventure trips, as well as niche and special interest products.
1. Introduction -- 2. The package holiday and the rise of the tour operator -- 3. The operating environment -- 4. Product development -- 5. Small and medium sized tour operators -- 6. Customer service -- 7. Financial planning : pricing the package -- 8. Tour operators and key travel regulations (with David Grant) -- 9. Distribution (place) -- 10. Marketing -- 11. Human resources and managing the workforce -- 12. Crisis management -- 13. A look ahead : challenges and issues.
Includes index.
Keywords: TOURISM -- MANAGEMENT